Strategies Used by English Teachers in Teaching Reading Comprehension - Arwila, Putu Pradana (Journal of Educational Study, 2022)
The purpose of the study was to recognize and to discover the application of the strategy used by the English teachers in teaching reading comprehension during online learning for seventh-grade students at SMPN 2 Singaraja. The research design used qualitative, with the research instruments in the form of observation and interview. The results of the research obtained were that the two English teachers used a question and answer strategy during the online learning process in teaching reading comprehension for seventh-grade students. Therefore, the strategy taught students how to interpret what kinds of questions were asked of them, as well as where to discover the answers, in that way, allowing students to think about the texts they read. In addition, motivating them to think creatively and collaboratively while challenging them to use their thinking skill, so that interactions between the English teacher and students could occur properly during the online learning process.